Value challenges of the present: reflections about morally appropriate and religious faith - Horokholinska, Iryna (Ukrai͏̈ns'ke relihijeznavstvo, 2016)
The article by Iryna Horokholinska «Value challenges of the present: reflections about morally appropriate and religious faith» is aimed to the analysis of the moral and religious portrait of a modern person - in the conditions of globalization and secularization. Should we talk about the total secularization? Did the renaissance of religiosity really come to be? And what's important: what is the mission and strategy of the Church's actions in influencing the axiological self-determination of the modern person? As a Christian can be to a Christian, but not to be preserved in a culturally and mentally obsolete system of priorities for the regulation of personal life? These questions are precisely the markers in the search for the answer to the urgent question addressed to representatives of the Western (Christian?) Civilization - Quo Vadis?